2013
DOI: 10.1002/bjs.9197
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of stents versus angioplasty for the treatment of iliac artery occlusions (STAG trial)

Abstract: ISRCTN 48145465 (http://www.controlled-trials.com).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 17 publications
0
29
0
4
Order By: Relevance
“…The stent data for more complex lesions such as TASC C/D and other CTO lesions are also encouraging (Table II) [14,18,19,22,24]. According to two recent meta-analyses [18,19], immediate technical success rates for aorto-iliac intervention exceed 90%, with 4-5 year primary patency rates of 60-86%, secondary patency rates of 80-98%, and limb salvage rates of 98%.…”
Section: Angioplasty and Stentingmentioning
confidence: 97%
See 3 more Smart Citations
“…The stent data for more complex lesions such as TASC C/D and other CTO lesions are also encouraging (Table II) [14,18,19,22,24]. According to two recent meta-analyses [18,19], immediate technical success rates for aorto-iliac intervention exceed 90%, with 4-5 year primary patency rates of 60-86%, secondary patency rates of 80-98%, and limb salvage rates of 98%.…”
Section: Angioplasty and Stentingmentioning
confidence: 97%
“…Several studies have compared the outcomes of percutaneous transluminal angioplasty (PTA) with provisional stenting to primary stenting for both iliac stenosis and occlusions [20][21][22] The Dutch iliac stent trial found that PTA with provisional stenting (for a residual gradient of >10 mmHg) had similar results to primary stenting [9] However, this study excluded patients with more complex lesions (lesions >10 cm or CTO's >5 cm). By employing a provisional stenting strategy in the iliac artery, stent placement was avoided in 63% of the lesions.…”
Section: Angioplasty and Stentingmentioning
confidence: 99%
See 2 more Smart Citations
“…complexity of disease, the differing segments of iliac artery to be treated, and the use of either balloon-expandable or self-expanding nitinol stents. [90,91] Currently there are no randomized data available regarding comparing outcomes of aortoiliac stenting with these 2 types of stents. Self-expanding stents are good to avoid arterial rupture.…”
Section: Figure5 An Intraoperative Photograph Of a Right Femoral To mentioning
confidence: 99%